Jerzy Grotowski a chiński teatr poszukujący i tajwański teatr tańca - Łabędzka, Izabella (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
This paper is devoted to the reception of Jerzy Grotowski’s ideas of theatre and actors’ training system in China and Taiwan at the end of the twentieth century. The author analyses the scope of Grotowski’s influence on Chinese and Taiwanese theatre reformers, stage directors and actors/dancers at a specific moment of deep social, cultural and political transformations in Asia. She also tries to determine the main reasons for Grotowski’s popularity in mainland China and Taiwan in the 80s and 90s.